Microinjection molding of polyamide 6/carbon nanotube composites - Ferreira, Tânia (2015)
Microinjection molding of polymer composites with carbon nanotubes (CNT) requires previous production of the nanocomposites, often by melt extrusion. Each processing step has a thermo-mechanical effect on the polymer melt, conveying different properties to the final product. In this work, polyamide 6 and its composites with pristine and functionalized CNT (f-CNT) were processed by a mini twin-screw extrusion, followed by microinjection molding. The morphology induced on the polymer by each process was analyzed by differential scanning calorimetry and wide angle X-ray diffraction. Calorimetric analysis showed a secondary crystallization for the microinjected materials, absent for the extruded materials. The characterization of microinjected polyamide 6 by X-ray diffraction revealed a large contribution of the c phase to the total crystallinity, mainly in the skin region, while the nanocomposites and extruded materials were characterized by a larger contribution of the a phase. Functionalization of CNT did not affect significantly the polymer morphology compared to composites with pristine CNT.